PENGARUH INFLASI DAN BI RATE TERHADAP MARGIN MURABAHAH - Yunita Maulidina; Widya Febryari Anita (Jurnal Widya Akuntansi dan Keuangan, 2022)
Banks are known as financial institutions whose main activity is accepting demand deposits, savings and time deposits. In addition, the bank is also known as a place to exchange money, transfer money or accept all kinds of payments and deposits such as payments for electricity, telephone, water, taxes, tuition, and other payments. The purpose of this study is to determine and analyze the effect of inflation and the BI Rate partially and simultaneously on Murabahah Margin at Islamic Commercial Banks in Indonesia for the 2018-2020 period. This study uses a quantitative approach with a sample of 14 Islamic Commercial Banks in Indonesia. The analysis technique used is the Classical Assumption Test, Multiple Regression Test, and Hypothesis Testing which consists of a partial test (t test), and a simultaneous test (F test). The results of this study indicate that partially between inflation and the BI Rate has no significant effect on the Murabahah Margin. Simultaneously or simultaneously Inflation and BI Rate have no significant effect on Murabahah Margin at Islamic Commercial Banks in Indonesia for the 2018-2020 period.